Damages — Power of board to award (Relations industrielles / Industrial Relations, 1961)
SummaryBy a majority, the board in this case holds, first, that the question of whether a board of arbitration may or may not award damages is not one going to jurisdiction, but is a matter of the powers of a board once it is properly seised of the dispute under the collective agreement or under the relevant legislation.On the question of the power to award damages, it holds that this does not depend on the inclusion of a specific provision in the agreement. The object of the voluntary submission by the parties to arbitration of their disputes is that there shall be a final and binding settlement of the disputes, and a board of arbitration has an inherent power to award damages where any compensable loss is suffered by either party. By submitting to the board's adjudication the parties must be presumed to have intended to submit to a complete adjudication of the matter and a proper redress of any wrong suffered as a result of a breach by either party of its obligations under the agreement.Polymer Corporation Ltd and Oil, Chemical and Atomic Workers International Union Local 16 - 14 - Arbitration award, Nov. 10th 1959, Bora Laskin, Q.C., C.L. Dubin, Q.C., M. O'Brien.